Comparison of different battery models and equivalent circuit model optimization - Koponen, Ville (My University, 2025)
The world is moving in a direction where the use of renewable energy is intended to be increased in order to reduce environmental burden and move away from the use of fossil fuels. Batteries allow energy to be stored and released later when needed. Lithium-ion batteries (LIBs) are lightweight and energy-dense, which makes them very attractive for applications in electric cars, in portable devices such as phones and laptops, and in stationary energy storage. LIBs can be described using a variety of models, including electrochemical, data-driven, empirical, and equivalent circuit models. A good battery model is accurate, not complicated and can be used in many different applications. In particular, the equivalent circuit models (ECM) can accurately describe the operation of batteries, are not complex, and can be used in various applications such as in battery management systems. Parameters of the ECM need to be established towards individual battery chemistries. In this work the models for used for the description of LIBs are summarized. Four equivalent circuit models are selected and optimized for two most ubiquitous types of LIBs, namely lithium nickel manganese cobalt oxide (NMC) and lithium iron phosphate (LFP) batteries. The accuracy of the models is examined and discussed.
Keywords: lithium-ion batteries, battery models, equivalent circuit model, optimization